Training ain't performance - Stolovitch, Harold D.; Keeps, Erica J. (ASTD Press, 2004)
Training Aint Performance is a whimsical, entertaining, and solidly written book that takes on the subject of human performance. From its first chapter, Show Me the Money, to its concluding chapters, Hit or Myth: Separating Fact from Workplace Performance Fiction, readers are gently guided toward an understanding of human performance improvement and how to use it for real organizational value.
Includes bibliographical references
Keywords: Employees -- Training of; Organizational effectiveness; Performance; Performance technology; Inservice Training; Task Performance and Analysis; Personnel; Formation; Efficacité organisationnelle; Rendement au travail; Employees; Training of